Learning PowerShell 6 - Jones, Joshua B. (Packt Publishing, 2018)
"This video is designed to help you get up and running with PowerShell, taking you from the basics of installation to writing scripts and web server automation. This will act as an introduction to the central topics of PowerShell, from finding and understanding PowerShell commands and packaging code for reusability right through to a practical example of automating IIS. It also includes topics such as installation and setup, creating scripts, automating tasks, and using PowerShell to access data stores, registry, and file systems. You will explore the PowerShell environment and discover how to use cmdlets, functions, and scripts to automate Windows systems. Along the way, you'll perform data manipulation and solve common problems using basic file input/output functions. The potential topics could bewill be Commands, Scripts, Providers, Files and folders, Objects, Variables, Classes and Enumerations, Expressions, DSC and so on. By the end of this course, you'll be able to leverage your skills to effectively manage and administrate the system using PowerShell 6"--Resource description page